Effect of the 2012 US Preventive Services Task Force Recommendations on Prostate-Specific Antigen Screening in a Medicare Advantage Population. Issue 12 (26th December 2022) - Zhu, Yingying; Koethe, Benjamin; Ollendorf, Daniel A.; Wong, John B.; Neumann, Peter J.; Kim, David D.
Abstract : Background: In 2012, the US Preventive Service Task Force revised its recommendations for prostate-specific antigen (PSA) screening from "insufficient evidence" to "do not recommend" for men aged 70–74 while maintaining "do not recommend" for men aged 75+. Methods: Using the difference-in-difference approach, we evaluated whether the rate of change in the use of low-value PSA screening differed between the control group (men aged 75+, N=7, 856, 204 person–years) and the intervention group (men aged 70–74, N=5, 329, 192 person–years) enrolling in the Medicare Advantage plan without a history of prostate cancer within the OptumLabs Data Warehouse claims data (2009–2019). A generalized estimating equation logistic model was specified with independent variables: an intervention group indicator, a pre- and post-period (after 2012 Q2) indicator, index time, and interaction terms. We assumed a 12-month dissemination period. Results: Before the revised recommendation in 2012, the trends did not significantly differ between the 2 age groups with the odds of receiving PSA screening decreasing by 1.2% (95% confidence interval [1.0, 1.4%]) per quarter. However, the odds of receiving PSA screening increased by 3.0% [2.8, 3.2%] per quarter across both groups since the revision. There was no significant additional change in the trend for those aged 70–74 (0.1% [−0.2, 0.5%]). Conclusions: Although the 2012 US Preventive Service Task Force's recommendations were expected to only change behaviors among men aged 70–74, our analysis found that men aged 70–74 and aged 75+ exhibited similar trends from 2009 to 2019, including the increased use of low-value PSA screening since 2016. Multifaceted efforts to discourage low-value PSA screening would be important for a sustained impact.